Transforming Tradition in the Dance Drama Realizing Rama, 1997–2004: Documenting the Process of “Inter-Creation” in an ASEAN Production - Tiongson, Nicanor G. (Archīum Ateneo, 2019)
This article seeks to illumine two aspects of the pioneering production Realizing Rama (1997-2004), a collaboration among artists from the ASEAN. First, it will describe and critique the process of inter-creation among traditional and modern artists that gave birth to a production style that was palpably Southeast Asian in tonality, movement, and visuality without being stereotyped as “ethnic.” Second, it will explicate and evaluate the participation of ASEAN artists in the production and the changes they underwent in the process of creating and performing the work. This study will show that the creation of Realizing Rama paralleled the initial realization of an ASEAN performing arts aesthetics and the creation of a paradigm for the process of artistic creation in an ASEAN artistic community.